2009
DOI: 10.1016/j.dci.2008.07.013
|View full text |Cite
|
Sign up to set email alerts
|

Identification and molecular characterization of a complement C3 molecule in a lophotrochozoan, the Hawaiian bobtail squid Euprymna scolopes

Abstract: Examination of the EST database of the light organ of the Hawaiian bobtail squid Euprymna scolopes revealed a sequence with similarity to complement C3. RACE yielded the full open reading frame of this protein. Analysis of the resultant sequence revealed that Es-C3 (E. scolopes-C3) has conserved residues and domains known to be critical for C3 function. The gene encoding C3 was expressed in all tissues tested, indicating that its expression is widely distributed throughout the animal's body. Immunocytochemistr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
50
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 66 publications
(54 citation statements)
references
References 41 publications
3
50
0
1
Order By: Relevance
“…All deuterostome species analyzed thus far such as various vertebrates, urochordate sea squirt [13], cephalochordate lancelet and echinoderm sea urchin [2], possess both the C3 and A2M family members, whereas many protostome genomes deciphered thus far such as fly [14], mosquito [15], honeybee [16], parasitoid wasp [17], aphid [18], flour beetle [19], and Caenorhabditis elegans [20] possessed only the A2M family members. Among protostomes, only horseshoe crab [21,22], spider [6], tick [23], clam [24] and squid [25] were reported to possess the C3 family, indicating that the loss of the C3 family has occurred multiple times during the protostome evolution [6]. The loss of the C3 family also occurred at least once in cnidaria, since hydra has only the A2M family gene [26].…”
Section: Evolution Of the Tep Superfamilymentioning
confidence: 95%
“…All deuterostome species analyzed thus far such as various vertebrates, urochordate sea squirt [13], cephalochordate lancelet and echinoderm sea urchin [2], possess both the C3 and A2M family members, whereas many protostome genomes deciphered thus far such as fly [14], mosquito [15], honeybee [16], parasitoid wasp [17], aphid [18], flour beetle [19], and Caenorhabditis elegans [20] possessed only the A2M family members. Among protostomes, only horseshoe crab [21,22], spider [6], tick [23], clam [24] and squid [25] were reported to possess the C3 family, indicating that the loss of the C3 family has occurred multiple times during the protostome evolution [6]. The loss of the C3 family also occurred at least once in cnidaria, since hydra has only the A2M family gene [26].…”
Section: Evolution Of the Tep Superfamilymentioning
confidence: 95%
“…1), indicating that some defensive mechanism still exists within biofilms formed by mutualistic strains. These defenses may be coopted to avoid the squid host innate immune response, which is mostly comprised of hemocytes and macrophages (39,40). Future studies will focus on whether receptor-mediated phagocytosis in protozoa affects immune response evasion through biofilm formation.…”
Section: Discussionmentioning
confidence: 99%
“…Although the C3 gene has been identified from all deuterostome species analyzed thus far (Nonaka, 2014), earlier genomic analyses showed its absence from the genomes of Drosophila melanogaster (Adams et al, 2000) and Caenorhabditis elegans (C. elegans Sequencing Consortium, 1998), indicating that this gene has been lost in at least some lineages of protostomes. On the other hand, the C3 gene has been reported from several other protostome species, such as the clam (Prado-Alvarez et al, 2009), the squid (Castillo et al, 2009), horseshoe crabs (Ariki et al, 2008;Zhu et al, 2005), the spider (Sekiguchi et al, 2012) and ticks (Buresova et al, 2011;Urbanová et al, 2015), and FB has also been reported from the clam (Prado-Alvarez et al, 2009) and horseshoe crab (Tagawa et al, 2012;Zhu et al, 2005). However, to date, no comprehensive analysis of the complement genes has been performed in protostome species possessing the C3 gene and it is still an unsolved question as to whether the protostome complement system shares complement components other than C3 and FB with deuterostomes.…”
Section: Introductionmentioning
confidence: 98%